Paradoxical regulation of human FGF21 by both fasting and feeding signals: is FGF21 a nutritional adaptation factor? - Takashi Uebanso; Yutaka Taketani; Hironori Yamamoto; Kikuko Amo; Hirokazu Ominami; Hidekazu Arai; Yuichiro Takei; Masashi Masuda; Ayako Tanimura; Nagakatsu Harada; Hisami Yamanaka-Okumura; Eiji Takeda (PLoS ONE, 2011)
Fibroblast growth factor 21 (FGF21) has recently emerged as a metabolic hormone involved in regulating glucose and lipid metabolism in mouse, but the regulatory mechanisms and actions of FGF21 in humans remain unclear. Here we have investigated the regulatory mechanisms of the human FGF21 gene at the transcriptional level. A deletion study of the human FGF21 promoter (-1672 to +230 bp) revealed two fasting signals, including peroxisome proliferator-activated receptor α (PPARα) and glucagon signals, that independently induced human FGF21 gene transcription in mouse primary hepatocytes. In addition, two feeding signals, glucose and xylitol, also dose-dependently induced human FGF21 gene transcription and mRNA expression in both human HepG2 cells and mouse primary hepatocytes. FGF21 protein expression and secretion were also induced by high glucose stimulation. The human FGF21 promoter (-1672 to +230 bp) was found to have a carbohydrate-responsive element at -380 to -366 bp, which is distinct from the PPAR response element (PPRE). Knock-down of the carbohydrate response element binding protein by RNAi diminished glucose-induced human FGF21 transcription. Moreover, we found that a region from -555 to -443 bp of the human FGF21 promoter region exerts an important role in the activation of basic transcription. In conclusion, human FGF21 gene expression is paradoxically and independently regulated by both fasting and feeding signals. These regulatory mechanisms suggest that human FGF21 is increased with nutritional crisis, including starvation and overfeeding.